WCDMA : towards IP mobility and mobile internet - Ojanperä, Tero; Prasad, Ramjee (Artech House universal personal communications series., 2001)
While covering the basics of wideband CDMA, this major revision of the best-selling Wideband CDMA for Third Generation Mobile Communications brings you up-to-date with all the latest developments in third generation mobile communications. New sections cover fundamental IP concepts, All-IP core networks, and the standardized radio access technologies WCDMA, EDGE and cdma2000, including their future developments - WCDMA HSPA and 1XEV.